Differences in Nutritional Quality, Resistant Starch, and Fiber of Mangpis Cookies Made from Lindur Flour (Bruguiera Gymnorhiza) and Saba Banana Flour (Musa Paradisiaca L.) - Liean Ahmad Ntau; Fatmayanti Nawai; Rahma Labatjo (Jurnal Indonesia Sosial Sains, 2026)
Obesity and diabetes mellitus remain major global health challenges associated with unhealthy dietary patterns, excessive energy intake, and inadequate fiber consumption. The development of functional food products containing dietary fiber and resistant starch is considered an effective nutritional strategy to support metabolic health. This study aimed to determine differences in nutritional quality, resistant starch content, and fiber characteristics of Mangpis Cookies formulated with lindur fruit flour (Bruguiera gymnorhiza) and kepok banana flour (Musa paradisiaca L.). This research used a laboratory experimental method with a completely randomized design consisting of four formulations: F0 (100% wheat flour), F1 (70% lindur flour:30% kepok banana flour), F2 (50% lindur flour:50% kepok banana flour), and F3 (30% lindur flour:70% kepok banana flour). Nutritional composition analysis included moisture, ash, protein, fat, carbohydrate, energy, resistant starch, crude fiber, and dietary fiber using standard analytical methods. The results showed that flour substitution significantly affected all nutritional parameters (p<0.05). Formula F1 demonstrated the highest functional nutritional characteristics, with resistant starch content of 8.10%, crude fiber of 7.64%, and dietary fiber of 9.06%. The findings indicate that lindur flour contributes substantially to increasing fiber and resistant starch levels in cookies, while kepok banana flour contributes to mineral content and nutritional diversification. In conclusion, Mangpis Cookies formulated with lindur and kepok banana flour have potential as a functional food product with improved nutritional properties, particularly for supporting healthier dietary patterns and metabolic health management.